ANALISIS SEKTOR UNGGULAN PERKEBUNAN KARET (STUDI KASUS ACEH TIMUR, ACEH TAMIANG DAN KOTA LANGSA) - Winda Maria Ulfa; Ernawati Ernawati (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
ABSTRACTThe purpose of this research is to analyze the level of development of the agricultural sector in the districts of East Aceh, Aceh Tamiang and Langsa City and analyze the rubber plantation sector of East, Aceh Tamiang and Langsa City.The data used are GRDP data for the agricultural sector in East District, Aceh Tamiang and Langsa City. To analyze the level of development of the rubber plantation sector using the Location Qoetient (LQ). The results of the analysis of the level of development of the agricultural sector of East rubber plantations, Aceh Tamiang and Langsa City are already classified as advanced. The East rubber plantation sector, Aceh Tamiang and Langsa City will become a developed sector and grow rapidly in Aceh Province, if the agricultural sector GRDP growth rate is higher than the Aceh Province GRDP growth rate, farmers and the business world need to increase added value (value added). ) Rubber plantation commodities so that their contribution and growth rate are increasing in the GRDP economy of East District, Aceh Tamiang and Langsa City.Keywords : Leading Sector Potential, Rubber Plantation, GRDP¸ location Quetiont